Multiplying Impact: The Role of Emotional Marketing in Mitigating Customer Revenge - Al-Hadrawi, Baqer Khudair; Shlafman, Natalia Leonidovna; Reniati, Reniati (International Journal of Magistravitae Management, 2024)
This study investigates the effectiveness of emotional marketing strategies in reducing instances of customer revenge, focusing on Fayd AL-Qassim Company in Al-Najaf Al-Ashraf as the applied context. Emotional marketing—characterized by personalized communication, empathetic customer service, and brand storytelling—plays a significant role in shaping customer perceptions and responses. By appealing to customers' emotions, companies can enhance satisfaction and loyalty, thereby reducing the likelihood of revengeful actions against the company. Using a descriptive-analytical approach, data were collected from employees of Fayd AL-Qassim Company. Statistical analysis conducted with SPSS v27 and Amos v24 revealed a significant correlation between emotional marketing efforts and revenge behaviors. The findings indicate that implementing emotional marketing techniques can provide substantial benefits for companies, not only by fostering positive customer relationships but also by protecting the company’s reputation and financial stability. This study contributes to the growing body of knowledge on the importance of emotional marketing in mitigating negative customer behaviors, highlighting its role in amplifying positive impacts on business outcomes.